Transport Infrastructure as a Basis for NATO Mobility in Europe: Key Directions and Formats for Development - T. Kh. Meloyan (Международная аналитика, 2025)
Since 2017, EU and NATO have been discussing the creation of “Military Schengen,” emphasizing the importance of integrating efforts to promptly respond to potential crises on the eastern flank of NATO. With aggravation of contradictions between Russia and the West in the context of the special military operation in Ukraine, this topic acquires even greater relevance. The aim of this study is to determine the role of transport infrastructures, primarily road and rail ones, on NATO’s military mobility in Europe and to examine the main areas and formats of cooperation in this area. Particular attention is paid to the projects of the Three Seas Initiative (Via Carpatia, Via Baltica, Rail-2-Sea), initiatives within the Trans-European Transport Network (TEN-T) and the Permanent Structured Cooperation (PESCO) programs. Based on the provisions of securitization theory, the author demonstrates mechanisms through which civilian projects acquire military significance, forming dual-use infrastructure. The author concludes that military mobility is becoming a key field for deepening cooperation between the EU and NATO and opens up new strategic opportunities for the alliance, facilitating the rapid transfer of troops and equipment to the Russian borders amid geopolitical tensions. The target task of the EU and NATO is to create a fully functioning transport infrastructure in Europe by 2030 to meet their military needs.In the medium term, this may create additional challenges for Russia. Accordingly,  the article suggests several ways of responding to them.